Miniaturized Cultivation of Microbiota for Antimalarial Drug Discovery. Issue 1 (26th December 2014) - Waterman, Carrie; Calcul, Laurent; Beau, Jeremy; Ma, Wai Sheung; Lebar, Matthew D.; von Salm, Jacqueline L.; Harter, Charles; Mutka, Tina; Morton, Lindsay C.; Maignan, Patrick; Barisic, Betty; van Olphen, Alberto; et al.
Abstract: The ongoing search for effective antiplasmodial agents remains essential in the fight against malaria worldwide. Emerging parasitic drug resistance places an urgent need to explore chemotherapies with novel structures and mechanisms of action. Natural products have historically provided effective antimalarial drug scaffolds. In an effort to search nature's chemical potential for antiplasmodial agents, unconventionally sourced organisms coupled with innovative cultivation techniques were utilized. Approximately 60, 000 niche microbes from various habitats (slow‐growing terrestrial fungi, Antarctic microbes, and mangrove endophytes) were cultivated on a small‐scale, extracted, and used in high‐throughput screening to determine antimalarial activity. About 1% of crude extracts were considered active and 6% partially active (≥67% inhibition at 5 and 50 μg/mL, respectively). Active extracts (685) were cultivated on a large‐scale, fractionated, and screened for both antimalarial activity and cytotoxicity. High interest fractions (397) with an IC50 < 1.11 μg/mL were identified and subjected to chromatographic separation for compound characterization and dereplication. Identifying active compounds with nanomolar antimalarial activity coupled with a selectivity index tenfold higher was accomplished with two of the 52 compounds isolated. This microscale, high‐throughput screening project for antiplasmodial agents is discussed in the context of current natural product drug discovery efforts.